1999
DOI: 10.1016/s0920-5861(99)00135-2
|View full text |Cite
|
Sign up to set email alerts
|

New insights into methanol synthesis catalysts from X-ray absorption spectroscopy

Abstract: X-ray absorption spectroscopic studies from several different groups provide a consistent structural picture of methanol synthesis catalysts. Copper metal is the principal Cu species detected in all in-situ XAS studies. A small amount of Cu(II) persisted in many samples reduced below 600 K, but it appears to be catalytically irrelevant. Cu(I) was not detected in any of the in-situ XAS studies. The Zn structure did not change in response to chemical treatments in any of the ZnO-containing methanol synthesis cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 47 publications
4
40
1
Order By: Relevance
“…37 On the other hand, Lee et al 34 reported that steady-state rates were reached in catalytic experiments with a Cu/ZnO/ Al 2 O 3 catalyst after 5 and 20 h on stream for CO 2 /H 2 and CO/H 2 , respectively. A similar transient behavior has also been observed by Meitzner and Iglesia 33,35 for Cu/SiO 2 . The catalytic activity decreased gradually when they were feeding CO 2 to a CO/H 2 /N 2 mixture.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…37 On the other hand, Lee et al 34 reported that steady-state rates were reached in catalytic experiments with a Cu/ZnO/ Al 2 O 3 catalyst after 5 and 20 h on stream for CO 2 /H 2 and CO/H 2 , respectively. A similar transient behavior has also been observed by Meitzner and Iglesia 33,35 for Cu/SiO 2 . The catalytic activity decreased gradually when they were feeding CO 2 to a CO/H 2 /N 2 mixture.…”
Section: Discussionsupporting
confidence: 86%
“…Similar behavior observed for binary and ternary Cu systems has been reported in the literature. [33][34][35] The highpressure measurements were conducted over a lowtemperature range from 433 to 513 K. The resulting production rates calculated from the outlet CH 3 OH concentration assuming differential conditions are displayed versus the inverse temperature in a so-called Arrhenius plot (Figure 4). It can be seen that the differences in the production rates of the three catalysts are small.…”
Section: Temperature-programmed Reaction Of Gasphase H 2 With Preadsomentioning
confidence: 99%
“…Iglesia and coworkers suggested that most of the MoC x species should be resided in the channels [24][25][26][27][28][29]. This opinion has been further demonstrated with 1 H MAS NMR measurements on the Mo/HZSM-5 catalysts prepared by impregnation by Bao and coworkers [30].…”
Section: Introductionmentioning
confidence: 88%
“…(vi) Cu + ions are active sites for CO adsorption and hydrogenation reactions [9,10,20]. The Cu + may be stabilized at the Cu/ZnO interface or are found as dissolved Cu in the ZnO particles [2,17,[21][22][23][24]. As pointed out by Nakamura et al more than one synergetic effect between Cu and ZnO may explain the high efficiency of this catalyst for methanol synthesis.…”
Section: Introductionmentioning
confidence: 92%